2016
DOI: 10.1177/0022427816664118
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of School Dropout among Serious Adolescent Offenders

Abstract: Objectives: Drawing on labeling and routine activities perspectives, this study investigates whether within-individual change in the school dropout status is associated with the risk of subsequent offending and arrest among serious adolescent offenders. Methods: Longitudinal panel data and a modified version of conventional random-effects models are used as a potential outcome model of causality to directly compare the outcomes before and after the change in the school dropout status. Results: School dropout s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
0
28
1
Order By: Relevance
“…An important result of this study is the link between the reasons for dropping out and delinquency. A few studies have examined the effect of the reasons for leaving school on delinquency ( Laub and Sampson, 2003 ; Na, 2017 ). According to the results of this study, it is estimated that students who leave school for personal reasons (e.g., general education development test) are unlikely to become delinquents when compared to students who leave school for academic reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important result of this study is the link between the reasons for dropping out and delinquency. A few studies have examined the effect of the reasons for leaving school on delinquency ( Laub and Sampson, 2003 ; Na, 2017 ). According to the results of this study, it is estimated that students who leave school for personal reasons (e.g., general education development test) are unlikely to become delinquents when compared to students who leave school for academic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, life-course perspective analyzes human behavior within structural, social, and cultural contexts. Based on the theory, school dropout might lead to delinquency, and the effect of school dropout on delinquency may vary depending on the reason and circumstances of dropping out ( Sweeten et al, 2009 ; Na, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The link between educational level and criminal offending in adolescents has been well established. Although there is general consensus that numerous risk factors (individual, family, peers, school, and neighborhood) all contribute cumulatively to criminal behavior (Wasserman et al, 2003), school achievement (usually indicated by factors such as poor school performance, low academic aspirations, peer rejection, and poor bonding to school) is particularly influential (Agnew, 2015; Katsiyannis, Ryan, Zhang, & Spann, 2008; Lynam, Moffitt, & Stouthamer-Loeber, 1993; Na, 2017). The characteristics of youth in juvenile justice residential placement bear witness to the link between school adjustment and serious or persistent criminal offending.…”
Section: Education Employment and Juvenile Justice Involvementmentioning
confidence: 99%
“…Dropouts are less likely to find employment and are more likely to end up earning lower wages. There is also evidence that school dropout is a predictor of delinquency, violence and drug use during adolescence and early adulthood ( Henry et al, 2012 ; Na, 2016 ).…”
Section: Introductionmentioning
confidence: 99%